2017
DOI: 10.1177/1524838017697268
|View full text |Cite
|
Sign up to set email alerts
|

Better Together? A Review of Evidence for Multi-Disciplinary Teams Responding to Physical and Sexual Child Abuse

Abstract: Multi-Disciplinary teams (MDTs) have often been presented as the key to dealing with a number of intractable problems associated with responding to allegations of physical and sexual child abuse. While these approaches have proliferated internationally, researchers have complained of the lack of a specific evidence base identifying the processes and structures supporting multi-disciplinary work and how these contribute to high-level outcomes. This systematic search of the literature aims to synthesize the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 49 publications
(122 reference statements)
0
28
0
3
Order By: Relevance
“…; McDonald, Scrum, and Rooney ). A recent review found evidence that multidisciplinary teams are more effective in improving mental health compared to standard practice (Herbert and Bromfield ). Collaboration between law enforcement and CP professionals (Cross, Finkelhor, and Ormrod ), and between CMH and CP professionals (Bai, Wells, and Hillemeier ), has been shown to improve coordination of investigations and to benefit children.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…; McDonald, Scrum, and Rooney ). A recent review found evidence that multidisciplinary teams are more effective in improving mental health compared to standard practice (Herbert and Bromfield ). Collaboration between law enforcement and CP professionals (Cross, Finkelhor, and Ormrod ), and between CMH and CP professionals (Bai, Wells, and Hillemeier ), has been shown to improve coordination of investigations and to benefit children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is the reasoning behind the establishment of Child and Youth Advocacy Centres (CYAC), which centralize all the necessary services for child victims (Herbert and Bromfield 2016;Jones et al 2007;McDonald, Scrum, and Rooney 2013). A recent review found evidence that multidisciplinary teams are more effective in improving mental health compared to standard practice (Herbert and Bromfield 2017). Collaboration between law enforcement and CP professionals (Cross, Finkelhor, and Ormrod 2005), and between CMH and CP professionals (Bai, Wells, and Hillemeier 2009), has been shown to improve coordination of investigations and to benefit children.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The searches identified 476 records for screening, of which three [129][130][131] were eligible for inclusion ( Figure 16).…”
Section: The Nature Of Co-ordination Problemsmentioning
confidence: 99%
“…We identified good evidence about the nature of co-ordination problems. Table 13 lists three literature reviews [129][130][131] and three primary observational studies 132-134 that were not cited in the reviews. The three reviews [129][130][131] used different methods and focused on different topics.…”
Section: The Nature Of Co-ordination Problemsmentioning
confidence: 99%
“…Araştırmalar, mağdur çocuğa yaklaşımda karşılaşılan sorunların çözümünde de farklı uzmanlık alanlarından gelenlerin bir arada müdahalesinin çocuğun yüksek yararı için önemini vurgulamaktadır. 19,20 Bu bağlamda çalışmamız sonucunda, ülkemiz içinde mağdur çocuğa yaklaşım ve müdahalede farklı uzmanlık alanlarının birbirlerinin görev ve sorumluluklarını tanıyan, birbirlerine saygı duyan, etkili iş birliği ve uyum içinde hareket eden bir bütünü oluşturması önerilmektedir. Böylelikle sorunların üstesinden gelmek ve mağdur çocuğun adalet mekanizması içerisinde hak ettiği muameleyi görmesi adına atılacak ilk adım olduğu düşünülmektedir.…”
Section: Tartişma Ve Sonuçunclassified